CHARACTERISTIC OF IATROGENIC BLADDER TRAUMA PATIENT IN HASAN SADIKIN GENERAL HOSPITAL FROM JANUARY 2013 - JANUARY 2018 - Karim, Muhammad Ilhamul; Adi, Kuncoro (Indonesian Journal of Urology, 2020)
Objective: This study was conducted to determine the characteristics of iatrogenic bladder trauma in Hasan Sadikin General Hospital from January 2013 – January 2018. Material & Methods: The study was conducted by retrospective descriptive methods. We reviewed iatrogenic bladder trauma from medical record at Hasan Sadikin General Hospital from January 2013 to January 2018. The data obtained is subsequently recapitulated and processed using a spreadsheet. Results: Most of the cases were found in female patients. There were 30 cases (73.17%) are recorded. Whilst on male patients, there were only 11 cases (26.83%). The average age was 42.35±2.35 years old. According to AAST grading, a total of 2 patients (4.88%) experienced AAST grade V, 28 patients (68.29%) experienced AAST grade IV, 8 patients (19.51%) experienced AAST grade III, and 3 patients (7.31%) experienced AAST grade I. In addition, there were 31 (75.61%) iatrogenic injuries due to gynecologic surgery, 6 (14.63%) iatrogenic injuries due to digestive surgery, and 4 (9.76%) iatrogenic injuries due to endourology surgery. Of all cases, 30 patients (73.17%) underwent immediate intraoperative reconstruction surgery, whilst the other 11 (26.83%) underwent delayed reconstruction surgery. As for the management, 33 (80.49%) patients underwent bladder repair, 1 (2.44%) patients underwent palliative cystectomy, 2 (4.88%) patients underwent damage control surgery, 3 (7.32%) patients underwent bladder exploration, and 2 (4.88%) patients underwent urethral catheter insertion. From all of 41 cases of patients with iatrogenic bladder injury, there were 3 (7.32%) mortality cases due to prolonged bleeding and sepsis. Conclusion: In this study, iatrogenic bladder trauma mostly affected female patients that underwent gynecologic surgery on the age group of 41-50 years old. Almost all of the cases were treated by bladder repair. By knowing the epidemiology of iatrogenic bladder injury and perform prompt treatment then we can take precautions to reduce the level of morbidity and mortality.